2015
DOI: 10.1016/j.apsusc.2015.05.054
|View full text |Cite
|
Sign up to set email alerts
|

A new tool for differentiating hepatocellular cancer cells: Patterned carbon nanotube arrays

Abstract: We aimed to develop a new approach to detect the invasiveness and metastatic degree of hepatocellular carcinoma cells (HCC) based on their epithelial mesenchymal transition (EMT) status by using patterned carbon nanotubes (CNT) without any further surface functionalization. We used well differentiated HUH7 and poorly differentiated SNU182 cells to examine and compare their adhesive features on patterned CNTs. We found that the well differentiated HUH7 cells attached significantly more on the patterned CNTs tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The listed studies in Table 1 can be divided into four main groups according to the used cells types: cells related to nervous system, 14,96,98–109 osteoblasts, 81,83,84,96,110–112 fibroblasts, 84,96,107,111,113–119 and other types. 84,97,119–127…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The listed studies in Table 1 can be divided into four main groups according to the used cells types: cells related to nervous system, 14,96,98–109 osteoblasts, 81,83,84,96,110–112 fibroblasts, 84,96,107,111,113–119 and other types. 84,97,119–127…”
Section: Resultsmentioning
confidence: 99%
“…84,96,97 The listed studies in Table 1 can be divided into four main groups according to the used cells types: cells related to nervous system, 14,96,[98][99][100][101][102][103][104][105][106][107][108][109] osteoblasts, 81,83,84,96,[110][111][112] broblasts, 84,96,107,111,[113][114][115][116][117][118][119] and other types. 84,97,[119][120][121][122][123][124][125][126][127] In the case of neurons, glia or cortical cultures growth, each study demonstrated a successful outcome. Thus, in 2000 the rst attempts were made to study the interface between CNTs and living systems.…”
Section: Impact Of Cnts Applied On Substratesmentioning
confidence: 92%
“…In another study, it was found that due to the invasive properties of hepatocellular carcinoma cells highly differentiated cells (HUH7) have a better chance of attachment than poorly differentiated cells (SNU182). Using this property Kucukayan-Dogu et al ( Kucukayan-Dogu et al, 2015 ) developed an imageable carbon nanotube surface and analyzed the ability of differentiated cells to attach to the imageable carbon nanotube surface. It can be used to diagnose the level of invasion of liver ( Figure 3A ) cancer cells.…”
Section: The Role Of Carbon Nanotubes In Cancer Diagnosismentioning
confidence: 99%